Characterization of temperature-dependent tension-compression asymmetry for high-strength aluminium alloys - Hetz, Peter; Merklein, Marion (Production at the leading edge of technology. Proceedings of the 9th Congress of the German Academic Association for Production Technology (WGP), 2019)
In the course of lightweight construction, modern materials with high strength and low density are essential. High-strength aluminium alloys such as 7000 series aluminium alloys meet these requirements but are only limited formable at room temperature. Thus, different heat assisted sheet metal forming processes are used to increase the formability. First investigations on the highstrength aluminium alloy AA7075 show a temperature-dependent and tensilecompressive asymmetric material behaviour. Since both tensile and compressive forces occur in sheet metal forming processes, an understanding of temperaturedependent tension-compression asymmetry is vital to set up material models for process design. Until now, the tension-compression asymmetry has barely been investigated for high-strength aluminium alloys at different temperatures. Therefore, further experimental studies are necessary. Within this contribution, the material behaviour of AA7020-T6 and AA7075-T6 is hence examined under uniaxial tensile and compressive load at different temperatures. For this purpose, both tensile and compressive tests are carried out on flat specimens between room temperature and 200 °C.<br
Keywords: Tension-compression asymmetry; High-strength aluminium alloy; Warm forming